2022
DOI: 10.1002/macp.202200124
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ion Transport in Novel Protic Polymerized Ionic Liquids and Composites

Abstract: In this work, a novel protic polymerized ionic liquid [PSTFSI][Im] is synthesized. The [PSTFSI][Im] polymer presents moderate ionic conductivity and evidences proton activity. Incorporating protic ionic liquid (Protic IL) [MIm][TFSI], the composites present enhanced ionic conductivity, up to 10 −3 S cm −1 at 120 °C upon addition of 60 wt% [MIm][TFSI]. It is found that the [PSTFSI][Im] polymer matrix can promote ion dissociation of the [MIm][TFSI] IL, leading to a larger cation/anion relative mobility compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…were confirmed by NMR spectroscopy as reported in our previous studies, 11,25 where no impurity peaks can be identified from the 1 H/ 19 F/ 13 C NMR spectra.…”
Section: The Purities Of [Mim][tfsi] and [Pstfsi][im]supporting
confidence: 88%
See 4 more Smart Citations
“…were confirmed by NMR spectroscopy as reported in our previous studies, 11,25 where no impurity peaks can be identified from the 1 H/ 19 F/ 13 C NMR spectra.…”
Section: The Purities Of [Mim][tfsi] and [Pstfsi][im]supporting
confidence: 88%
“…Nanosilica (Sigma-Aldrich, 14 nm), acetonitrile (Sigma-Aldrich, ≥99.8%), and methanol (Sigma-Aldrich, ≥99.8%) were commercially available and used without any further pretreatment. [PSTFSI]­[Im] and [MIm]­[TFSI], as shown in Figure , were synthesized as per published methods . The purities of [MIm]­[TFSI] and [PSTFSI]­[Im] were confirmed by NMR spectroscopy as reported in our previous studies, , where no impurity peaks can be identified from the 1 H/ 19 F/ 13 C NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations